Optic neuritis: current challenges in diagnosis and management - Benard-Seguin, Etienne; Costello, Fiona (Current opinion in neurology, 2023)
The primary aim of this review is to describe the clinical course, salient imaging features, and relevant serological profiles of common optic neuritis (ON) subtypes. Key diagnostic challenges and treatment options will also be discussed. ON is a broad term that describes an inflammatory optic nerve injury arising from a variety of potential causes. ON can occur sporadically, however there is particular concern for co-associated central nervous system (CNS) inflammatory syndromes including multiple sclerosis (MS), neuromyelitis optic spectrum disorders (NMOSD), and myelin oligodendrocyte glycoprotein antibody associated disease (MOGAD). The ON subtypes that often herald MS, NMOSD, and MOGAD differ with respect to serological antibody profile and neuroimaging characteristics, yet there is significant overlap in their clinical presentations. A discerning history and thorough examination are critical to rendering the correct diagnosis. Optic neuritis subtypes vary with respect to their long-term prognosis and accordingly, require different acute treatment strategies. Moreover, delays in identifying MOGAD, and certainly NMOSD, can be highly detrimental because affected individuals are vulnerable to permanent vision loss and neurologic disability from relapses.